Practice Questions in Trauma and Orthopaedics for the FRCS. - Sharma, Pankaj (Master pass., 2016)
This book includes a foreword by Nicola Maffulli, Professor of Trauma and Orthopaedic Surgery, Keele University School of Medicine, and Consultant Trauma and Orthopaedic Surgeon, North Staffordshire Royal Infirmary and City General Hospital, Staffordshire. The new structure of the Fellowship of the Royal College of Surgeons (FRCS) examination requires candidates to complete two papers in extended matching question (EMQ) and multiple choice question (MCQ) format. This invaluable revision aid contains a 'bank' of over 350 questions in self-test format. Comprehensive answers are detailed at the end of each section. With a focus on high-yield topics, students can choose use the resource in the early stages as an overview of the subjects, then later as an ideal exam revision aid. There's nothing else like it! Specialist registrars preparing for the FRCS (Trauma and Orthopaedics) examination will find this an essential revision aid. It is also useful for Basic Surgical Trainees preparing for the Membership of the Royal College of Surgeons (MRCS) examination.